Senior Team Attributes and Organizational Ambidexterity: The Moderating Role of Transformational Leadership - Jansen, Justin J. P.; George, Gerard; Van den Bosch, Frans A. J.; Volberda, Henk W. (Journal of Management Studies, 2008)
abstract Organizations capable of pursuing exploration and exploitation simultaneously have been suggested to obtain superior performance. Combining both types of activities and achieving organizational ambidexterity, however, leads to the presence of multiple and often conflicting goals, and poses considerable challenges to senior teams in ambidextrous organizations. This study explores the role of senior team attributes and leadership behaviour in reconciling conflicting interests among senior team members and achieving organizational ambidexterity. Findings indicate that a senior team shared vision and contingency rewards are associated with a firm's ability to combine high levels of exploratory and exploitative innovations. In addition, our study shows that an executive director's transformational leadership increases the effectiveness of senior team attributes in ambidextrous organizations and moderates the effectiveness of senior team social integration and contingency rewards. Hence, our study clarifies how senior executives reconcile conflicting demands and facilitate the balancing of seemingly contradictory forces in ambidextrous organizations. Implications for literatures on senior team attributes, transformational leadership and organizational ambidexterity are discussed.